2017
DOI: 10.3389/fpls.2017.01523
|View full text |Cite
|
Sign up to set email alerts
|

Soil Biological Activity Contributing to Phosphorus Availability in Vertisols under Long-Term Organic and Conventional Agricultural Management

Abstract: Mobilization of unavailable phosphorus (P) to plant available P is a prerequisite to sustain crop productivity. Although most of the agricultural soils have sufficient amounts of phosphorus, low availability of native soil P remains a key limiting factor to increasing crop productivity. Solubilization and mineralization of applied and native P to plant available form is mediated through a number of biological and biochemical processes that are strongly influenced by soil carbon/organic matter, besides other bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 89 publications
(98 reference statements)
2
23
2
Order By: Relevance
“…The values of the ACP activity found in this study are within the optimal ranges of phosphatase activity published by Bhat et al (2017). mediated soil processes, as reported by Stott, Andrews, Liebig, Wienhold, and Karlen (2010).…”
Section: Acid Phosphatasesupporting
confidence: 90%
See 3 more Smart Citations
“…The values of the ACP activity found in this study are within the optimal ranges of phosphatase activity published by Bhat et al (2017). mediated soil processes, as reported by Stott, Andrews, Liebig, Wienhold, and Karlen (2010).…”
Section: Acid Phosphatasesupporting
confidence: 90%
“…The values for the DHA activity in the substrates evaluated in this study are greater than those reported by Bhat et al (2017) for soils under organic production. Figure 4b presents the results of ACP activity (μg pnitrophenol g soil −1 hr −1 ) (10 evaluations).…”
Section: Dehydrogenasecontrasting
confidence: 77%
See 2 more Smart Citations
“…A smaller proportion of soil P is in the microbial biomass and can play a major role in P availability when the turnover time is short [22]. For instance, the rate of microbial P cycling is generally greater in organically managed soils compared to conventional soils because of greater manure additions in organic systems [15,23]. Since, plants can only take up orthophosphate ions (H 2 PO 4…”
Section: P Availability In Soilsmentioning
confidence: 99%